EMERGENCY ESCAPE DEVICE - KWON, YOUNG CHEOL (2018)
The present invention relates to an emergency escape device, and more specifically relates to an emergency escape device, comprising: an upside down U shaped body portion being insertable by a rail; a support portion formed to have an angle in one corner between two corners formed in the body portion; and a fastening portion formed in one end of the support portion and fastening a hook. Therefore, the emergency escape device can be simply installed in a window frame and people are able to quickly and safely escape from a building. 본 발명은 비상 탈출 장치에 관한 것으로, 더욱 상세하게는 레일이 삽입되도록 ''형상으로 형성되는 바디부; 상기 바디부에 형성된 두 모서리 중 하나의 모서리에 각도를 갖도록 형성된 지지부; 및 상기 지지부의 일단에 형성되어 후크를 체결하도록 하는 체결부를 포함한다.